Transformasi Zakat Digital: Strategi Akselerasi Pengentasan Kemiskinan di Era Society 5.0 - Fredi Setyono; Haikal Firmansah Anas Pratama (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The Society 5.0 era promotes the integration of cyber-physical technology through Artificial Intelligence (AI) and Big Data for human welfare, where digital zakat transformation becomes a crucial strategy to bridge the wide gap between national zakat potential (±IDR 327 trillion) and its actual collection. This study aims to analyze digital zakat transformation strategies in accelerating poverty alleviation in Indonesia within the smart society era. The research method employed is a descriptive qualitative approach using a library research method, analyzing literature from the 2020-2025 period sourced from digital databases. The results indicate that the implementation of digital technologies such as fintech platforms, blockchain, and QRIS significantly enhances transparency, accountability, and muzakki trust, while accelerating fund distribution time by up to 50%. Digital-based productive zakat strategies through MSME empowerment have proven effective in increasing mustahik's average income by up to 100%, facilitating the transformation of mustahik into independent muzakki. This study concludes that digital zakat transformation serves as a primary catalyst for achieving the first pillar of the Sustainable Development Goals (SDGs) (No Poverty), although its success requires national regulatory harmonization and the strengthening of technological infrastructure in rural areas.